The N400 is modulated by unconsciously perceived masked words: further evidence for an automatic spreading activation account of N400 priming effects - Kiefer, Markus (Brain research. Cognitive brain research, 2002)
It is a matter of debate whether the N400 component of the event-related brain potential (ERP) is sensitive to unconscious automatic priming mechanisms or to strategic mechanisms only. Recent studies demonstrated N400 modulation by masked primes at a short SOA supporting an automatic spreading activation account. However, it cannot be ruled out that strategic mechanisms based upon partial prime identification contributed to the observed priming effects. The present study was set up to substantiate masked N400 priming effects as an index of automatic spreading activation. It was assessed whether partial identification of the masked words due to backward priming could have supported strategic priming to occur. In experiment 1, ERPs were recorded while subjects performed lexical decisions on targets preceded by masked and unmasked primes at an SOA of 67 ms. Masked words, which were not consciously perceived, as well as visible words were shown to modulate the N400 to meaningfully related target words. Experiment 2 required subjects to perform decisions on visual, lexical and semantic features of masked words presented with or without semantically related context words. Subjects performed at chance in all tasks. Furthermore, the results exclude the possibility that backward priming has rendered the masked words partially visible. The present study therefore demonstrates that N400 priming effects can be reliably obtained from unconsciously perceived masked words at a very short SOA and strengthens the notion that the N400 is modulated by automatic spreading activation and not exclusively by strategic semantic processes.